The Gender Wage Gap Among University Vice Chancellors in the UK - Ray Bachan; Alex Bryson (Institute of Labor Economics (IZA), 2021)
The gender wage gap has closed gradually in the United Kingdom, as in other countries, but convergence is slower among top earners. Using linked employer-employee data over two decades we examine the gap among university Vice Chancellors who are among the most highly paid employees in the UK. Traditionally dominated by men the occupation has experienced a recent influx of women. The substantial gender wage gap of 12 log points in the first decade of the 21st Century closed markedly during the second decade, becoming statistically non-significant in later years. The closure in the gap is accounted for by change in the attributes of male and female VCs and the universities they lead - in particular, the financial performance of universities employing female VCs. The unexplained component of the gap is small and explains none of the convergence in the gap. A "new starter" wage penalty women faced in the early 2000s disappeared. However, women continued to receive a lower wage when replacing an outgoing male Vice Chancellor, whereas no differential was apparent between incoming male Vice Chancellors and the women they replaced.
Keywords: J16; J31; J44; 330; gender wage gap; vice chancellors; higher education; decompositions; linked employer-employee data